Oil sludge fuel mixtures with additives of fossil and biomass origin: Energy and operational parameters - Vershinina K. Yu. Kseniya Yurievna; Dorokhov V. V. Vadim Valerjevich; Romanov D. S. Daniil Sergeevich; Strizhak P. A. Pavel Alexandrovich (2025, 2025)
Title screen